The improvement and application of the criminal law on theft of property (Journal of actual problems of jurisprudence, 2018)
This article discusses the complex criminal law and criminological aspects of the problem of theft of property, of forms of ownership, rather than separately on the State and the public, on the one hand, and on the other, which is observed in previous studies. The author of the content of the concepts of «property», «right to property» and «patrimonial» actions. Also defined the relationship between them and assess the adequacy of the consideration of the last two as subjects of crimes. Disclosure of criminal law value of the object and the subject of crime of theft. Vyrabatano recommendations to improve the criminal law on theft of property.Key words: subject, object, crimes against property, the prevention of crimes against sobstsvennosti.